Bambara Groundnut: An Underutilized Leguminous Crop for Global Food Security and Nutrition - Xin Lin Tan; Xin Lin Tan; Susan Azam-Ali; Susan Azam-Ali; Ee Von Goh; Ee Von Goh; Maysoun Mustafa; Maysoun Mustafa; Hui Hui Chai; Hui Hui Chai; Wai Kuan Ho; Wai Kuan Ho; et al. (Frontiers in Nutrition, 2020)
Rapid population growth, climate change, intensive monoculture farming, and resource depletion are among the challenges that threaten the increasingly vulnerable global agri-food system. Heavy reliance on a few major crops is also linked to a monotonous diet, poor dietary habits, and micronutrient deficiencies, which are often associated with diet-related diseases. Diversification—of both agricultural production systems and diet—is a practical and sustainable approach to address these challenges and to improve global food and nutritional security. This strategy is aligned with the recommendations from the EAT-Lancet report, which highlighted the urgent need for increased consumption of plant-based foods to sustain population and planetary health. Bambara groundnut (Vigna subterranea (L.) Verdc.), an underutilized African legume, has the potential to contribute to improved food and nutrition security, while providing solutions for environmental sustainability and equity in food availability and affordability. This paper discusses the potential role of Bambara groundnut in diversifying agri-food systems and contributing to enhanced dietary and planetary sustainability, with emphasis on areas that span the value chain: from genetics, agroecology, nutrition, processing, and utilization, through to its socioeconomic potential. Bambara groundnut is a sustainable, low-cost source of complex carbohydrates, plant-based protein, unsaturated fatty acids, and essential minerals (magnesium, iron, zinc, and potassium), especially for those living in arid and semi-arid regions. As a legume, Bambara groundnut fixes atmospheric nitrogen to improve soil fertility. It is resilient to adverse environmental conditions and can yield on poor soil. Despite its impressive nutritional and agroecological profile, the potential of Bambara groundnut in improving the global food system is undermined by several factors, including resource limitation, knowledge gap, social stigma, and lack of policy incentives. Multiple research efforts to address these hurdles have led to a more promising outlook for Bambara groundnut; however, there is an urgent need to continue research to realize its full potential.